Research on intrinsic capacity as a predictor of falls and disability in community-dwelling elderly - Liu, Aihong; You, Yanjie; Wang, Yumei; Li, Ling; Yuan, Jinrong (Frontiers in Aging, 2025)
BackgroundWith aging, a decline in intrinsic capacity can lead to functional impairments, thereby increasing the risk of adverse health outcomes.ObjectivesThis study aims to explore the prediction of intrinsic capacity decline on adverse health outcomes, such as falls and disability, over the course of 1 year. By addressing the gap in longitudinal research on community populations in China, the study seeks to deepen the local understanding of healthy aging theory, providing theoretical support for the development of elderly health intervention strategies tailored to Chinese contexts.MethodsA convenience sampling method was employed to select 248 community-dwelling elderly participants. Over a 1-year follow-up period, the outcomes of falls and disability were monitored. Logistic regression analysis was used to evaluate the relationship between intrinsic capacity and these outcomes.ResultsAmong the 248 participants, 46 (19%) experienced falls, and 31 (12.8%) became disabled during the follow-up year. The locomotive dimension (OR = 25.87, 95% CI: 2.95–227.03), psychological dimension (OR = 25.29, 95% CI: 6.45–99.28), and sensory dimensions (OR = 10.75, 95% CI: 2.92–39.56) were identified as significant risk factors for falls. For disability, the locomotive dimension (OR = 4.15, 95% CI: 0.97–17.72), cognitive dimension (OR = 11.27, 95% CI: 3.51–36.18), and psychological dimension (OR = 4.58, 95% CI: 1.69–12.40) were significant risk factors.ConclusionDecline in intrinsic capacity serves as an independent predictor of both falls and disability among community-dwelling elderly individuals over the course of 1 year. Early identification of elderly individuals with decreased intrinsic capacity, along with targeted interventions based on different intrinsic capacity levels, can effectively reduce the incidence of falls and disability.